2017
DOI: 10.1016/j.rbmo.2017.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Duration of blastulation may be associated with ongoing pregnancy rate in single euploid blastocyst transfer cycles

Abstract: Not all euploid embryos implant, necessitating additional tools to select viable blastocysts in preimplantation genetic screening cycles. In this retrospective cohort study, 129 consecutive patients who underwent 129 single euploid blastocyst transfers in cryopreserved embryo transfer cycles were included. All embryos were individually cultured in a time-lapse incubator from intracytoplasmic sperm injection up to trophoectoderm biopsy. Twenty-three time-lapse morphokinetic variables were tested among patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…As such, this study indeed demonstrated that euploidy rate in oocyte donors is treatment center related. Studies have shown that suboptimal culture systems can affect gene expression and imprinting (Ho et al 1994Ho et al 1995; Doherty et al 2000; Fernandez-Gonzalez et al 2010; Market Velker et al 2010) demonstrating that embryonic chromosomal abnormality could be partly iatrogenic ( 5 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As such, this study indeed demonstrated that euploidy rate in oocyte donors is treatment center related. Studies have shown that suboptimal culture systems can affect gene expression and imprinting (Ho et al 1994Ho et al 1995; Doherty et al 2000; Fernandez-Gonzalez et al 2010; Market Velker et al 2010) demonstrating that embryonic chromosomal abnormality could be partly iatrogenic ( 5 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, experimental evidence and clinical data suggest that a number of treatment related factors may affect the incidence of chromosomal imbalance in embryos with exclusion of age ( 3 , 5 7 ). Factors such as culture conditions, gamete manipulation, high oxygen tension during culture, immaturity, and post maturity of oocytes at the point of fertilization ( 3 , 5 , 7 , 8 ) can possibly induce gene expression and chromosomal abnormalities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the former, biopsied trophectoderm samples were transferred to 1xPBS solution in PCR tubes, stored at −20 • C until 24 samples were collected, and then shipped to the central laboratory. Whole-genome amplification was performed using the Sureplex amplification kit (Illumina, San Diego, CA, USA) (35). After WGA, amplification was checked in gel electrophoresis, and DNA concentration was measured using the dsDNA high-sensitivity assay kit (Qubit R ; Life Technologies, Waltham, MA, USA).…”
Section: Trophectoderm Biopsy and Preimplantation Genetic Testingmentioning
confidence: 99%